[PP.11.14] PROGNOSTIC SIGNIFICANCE OF SLEEP APNEA SYNDROME ON FALSE LUMEN AORTIC EXPANSION IN POST ACUTE AORTIC SYNDROME. (September 2016) - Delsart, P.; Ramstein, J.; Juthier, F.; Sobocinski, J.; Rousse, N.; Jegou, B.; Fayad, G.; Modine, T.; Mallart, A.; Devos, P.; Vincentelli, A.; Haulon, S.; et al.
Abstract : Objective: Good blood pressure control is essential in patients with acute aortic syndrome (AAS). It has been shown that the obstructive sleep apnoea syndrome (OSAS) is a risk factor for resistant arterial hypertension, and aortic dilatation. Here, we assessed benefit of systematic screening for SAS in post AAS. Figure. No caption available. Design and method: We performed a prospective study of patients having undergone surgical treatment for AAS in our university medical centre between January 2010 and June 2014. The patients were screened for OSAS by a polygraphy record in a sleep clinic after the onset of AAS. The severity of OSAS was defined according to the apnoea hypopnoea index (AHI, per hour) and the oxygen desaturation index (ODI, per hour), using the following classes for both index: less than 5: no SAS; 6 to 15: mild SAS; 16 to 30; moderate SAS; upper than30: severe SAS. Blood pressure control was assessed by a 24 hour ambulatory blood pressure monitoring. Results: The population comprised 71 patients (males: 64.7%; median age: 57 [49–64], type A AAS: 49.3%; type B AAS: 50.7%). According to the AHI, 58 patients (81.7%) had OSAS and 31 (43.6%) had severe OSAS. The factors associated with the severity of OSAS were the body mass index (p = 0.0148 for the AHI and 0.009 for the ODI), abdominal perimeter (p = 0.0016 for the AHI and 0.0106 for the ODI). A prognostic analysis revealed a significant increase in the intrathoracic false lumen dilatation rate as a function of OSAS severity (p = 0.0008 for the AHI and p = 0.0284 for the ODI). The median rate of increase was 7.5 mm/year [5–10] in the AHI>30 group and 5.0 mm/year [0–8] in the ODI>30 group. There were no intergroup differences in blood pressure control according AHI category, but a diastolic blood pressure difference was noted for the ODI (p = 0.0008). Conclusions: Our results suggest that systematic screening for OSAS is of value in patients with AAS. The false lumen dilatation rate appears to be related to the severity of OSAS. It remains to be seen whether the treatment OSAS would modify the false lumen dilatation rate.